Research on the conservation practices employed by UPV-CM students, as household members, on their electricity and water consumption - Del Rosario, Amelle B.
This research seeks to determine the conversation practices employed by UPV-CM students, as household members, on their electricity and water consumption. The empirical findings show that as household members, UPV-CM students employ power-saving and water-saving techniques indicating a high level of awareness, in their usage of power and water. Most common techniques used in electricity consumption are : a) turning off lights when not uses, b) using flourescent lamp instead of an ordinary bulb, c) using electric fan instead of air-conditioner, d) refraining from opening the refrigerator for unnecessary purpose, e) turning off the electric iron several minutes before finishing. Most common techniques used in water consumption are : a) fixing leaking taps, b) using a glass of water instead of gushing faucet for brushing teeth , c) never letting a faucet drip.